2015
DOI: 10.1038/cddis.2015.151
|View full text |Cite
|
Sign up to set email alerts
|

Microglia-derived IL-1β triggers p53-mediated cell cycle arrest and apoptosis in neural precursor cells

Abstract: Neurogenesis persists in the adult brain and can contribute to learning and memory processes and potentially to regeneration and repair of the affected nervous system. Deregulated neurogenesis has been observed in neuropathological conditions including neurodegenerative diseases, trauma and stroke. However, the survival of neural precursor cells (NPCs) and newly born neurons is adversely affected by the inflammatory environment that arises as a result of microglial activation associated with injury or disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
78
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(83 citation statements)
references
References 68 publications
4
78
0
1
Order By: Relevance
“…Inflammatory actions of IL-1β are mediated by the type I IL-1 receptor (IL-1R). Recent evidence has shown that IL-1β decreases the proliferation and survival rates of neural precursor cells by activating IL-1β/IL-1R signaling and upregulating p53 and p53-mediated genes, which leads to cell cycle inhibition and Puma/Bax-mediated apoptosis in neural precursor cells (Guadagno et al , 2015). Moreover, increased IL-1β production by microglia and astrocytes is linked to upregulated expression of IL-1R on oligodendrocytes and increased apoptosis of oligodendrocytes in periventricular white matter of neonatal brain (Deng et al , 2014; Xie et al , 2016).…”
Section: Molecular Mediators Of Inflammation In Neonatal Hi Brain mentioning
confidence: 99%
“…Inflammatory actions of IL-1β are mediated by the type I IL-1 receptor (IL-1R). Recent evidence has shown that IL-1β decreases the proliferation and survival rates of neural precursor cells by activating IL-1β/IL-1R signaling and upregulating p53 and p53-mediated genes, which leads to cell cycle inhibition and Puma/Bax-mediated apoptosis in neural precursor cells (Guadagno et al , 2015). Moreover, increased IL-1β production by microglia and astrocytes is linked to upregulated expression of IL-1R on oligodendrocytes and increased apoptosis of oligodendrocytes in periventricular white matter of neonatal brain (Deng et al , 2014; Xie et al , 2016).…”
Section: Molecular Mediators Of Inflammation In Neonatal Hi Brain mentioning
confidence: 99%
“…Neurons release several inflammatory cytokines, such as interleukin (IL)-1β, tumor necrosis factor (TNF)-α, and IL-6 in response to infection by encephalitic flaviviruses, such as WNV and JEV [195]. As well as impairing BBB integrity [152], elevated levels of IL-1β can induce cell cycle arrest and apoptosis in neural precursor cells (NPCs) [196]. TNF-α impairs glutamate uptake by astrocytes, leading to neuronal death due to excitotoxicity [197].…”
Section: Neuropathogenesis Of Arbovirusesmentioning
confidence: 99%
“…Several studies indicate that IL-1β is antineurogenic (Koo and Duman, 2008;Ryan et al, 2013) by activation of the tumor suppressor p53 (Guadagno et al, 2015) or via adrenocortical activation (Goshen et al, 2008). Other findings suggest a proneurogenic effect of IL-1β (de la Mano et al, 2007;Xue et al, 2015).…”
mentioning
confidence: 99%